Valuing the Undervalued: Professional Development for Chairs and Adjuncts - STEPHEN BENTON; Ken Ryalls (Academic Chairpersons Conference Proceedings, 2015)
Department chairs and adjunct instructors share some things in common. They do much of the work but receive little recognition, and they frequently assume their professional roles under-prepared. What can be done to support their professional development? IDEA’s multi-faceted feedback system will be described followed by guided discussion.
Keywords: adjunct faculty; part-time faculty; faculty development; faculty evaluation; student ratings of instruction